Shah Alam City’s Current Restrictions on Flood Risk Management: Stakeholders Perspectives Review - Haziq Sarhan Rosmadi; Minhaz Farid Ahmed; Mokhtar Mazlin (E3S Web of Conferences)
Shah Alam, a city near the Klang River, is susceptible to flooding due to its urban transformation from oil palm plantations. Heavy rainfall, tropical storms, and flash floods have caused widespread flooding, landslides, power outages, disrupted water treatment plants, and port operations. The Malaysian government has faced criticism for its delayed response and apathy towards the disaster. This study aims to provide a unique perspective on flash flood problems and solutions in Shah Alam, focusing on the opinions and ideas of existing multi-stakeholder groups, particularly at the local level. Primary data was gathered through informal interviews and secondary data was obtained through a thorough examination of books, journals, research papers, and government reports. The thematic analysis of both primary and secondary data using Taguette tools found that the problem of disaster management in Shah Alam is related to inadequate proactive leadership roles of the local authority for coordination and collaboration among relevant agencies, as well as inadequate communication and data support systems. This leads to weaknesses in collaboration among agencies, making it difficult to carry out large-scale projects. Additionally, weaknesses in communication and information sharing are evident, where critical information such as weather forecasts are needed by rescue agencies to better prepare for disasters. Thus, the presence of NADMA in local level and a centralised data centre by the local authority with full cooperation from government agencies is important to improve the disaster management including flood risks.